Seroprevalence of Syphilis Infection among Apparently Clinically Healthy Blood Donors in Northern Mid - Karnataka - Kulkarni, Bhakti V; Bommanahalli, Basavaraj P; Pawadshettar, Rajshekhar T (Annals of Pathology and Laboratory Medicine, 2019)
Background: Blood transfusion is one of the important modalities of treatment in hospitals these days. Transfusion transmissible infections (TTI) are one of the important complications of blood transfusion. Objective: To study the seroprevalence of syphilis infection among healthy blood donors in our region Materials and methods: This is a retrospective study done over a period of 3 years from August 2015 to July 2018 in two blood banks of Gadag i.e. Gadag Institute of Medical Sciences (GIMS) blood bank and Indian Medical Association (IMA) blood bank. A total of 20,144 blood donors were included in the study. It included both voluntary donors and replacement donors. Donors were screened using donor questionnaire form followed by general physical examination for medical and surgical illness. Eligible blood donors donated blood and their blood samples were subjected to a test that detected the presence of non treponemal antibodies by using rapid plasma reagin (RPR) test kit. Result: In the present study, the total number of donors is 20,144. Out of this, 19,676 (97.67%) were males and 468 (2.33%) were females. Total number of seropositive cases of syphilis was 5. The overall seroprevalence was 0.023%. All the seropositive cases were males. The prevalence of seropositive cases among voluntary donors was 0% and among replacement donors was 0.14% Conclusion: Seroprevalence of syphilis in the region of Gadag is 0.023%.